The Relationship between Self-Management and Student Academic Procrastination - Zuhrah Zulmahdiyyah Sinaga; Nurmawati Nurmawati (Universitas Negeri Padang, 2023)
The purpose of this study was to determine the relationship between self-management and academic procrastination among students at SMA Negeri 1 Gunung Sindur. The approach used is a quantitative approach with a descriptive correlational model and data analysis techniques with Pearson product moment correlation. Sampling uses a sampling technique, namely probability sampling with proportionate random sampling. Data collection took the form of a self-management questionnaire and an academic procrastination questionnaire. The results of the study show that there is a positive, significant, and quite strong relationship between self-management and academic procrastination, as seen from the Pearson correlation of 0.557 and the sig value of 0.000. H0 is rejected and H1 is accepted. The results of the study in terms of the aspects of the self-management variable found that the indicators of student behavior were in the low category, while the academic procrastination variable on the aspect of the time gap between plans and actual performance was in the high category.